De novo Transcriptome Assembly of Myllocerinus aurolineatus Voss in Tea Plants - Xie, Xin; Jiang, Junmei; Chen, Meiqing; Huang, Maoxi; Jin, Linhong; Li, Xiangyang (Frontiers in Sustainable Food Systems, 2021)
Myllocerinus aurolineatus Voss is a species of the insecta class in the arthropod. In this study, we first observed and identified M. aurolineatus Voss in tea plants in Guizhou, China, where it caused severe quantity and quality losses in tea plants. Knowledge on M. aurolineatus Voss genome is inadequate, especially for biological or functional research. We performed the first transcriptome sequencing by using the Illumina Hiseq™ technique on M. aurolineatus Voss. Over 55.9 million high-quality paired-end reads were generated and assembled into 69,439 unigenes using the Trinity short read software, resulting in a cluster of 1,207 bp of the N50 length. A total of 69,439 genes were predicted by BLAST to known proteins in the NCBI database and were distributed into Gene Ontology (20,190), eukaryotic complete genomes (12,488), and the Kyoto Encyclopedia of Genes and Genomes (3,170). We also identified 96,790 single-nucleotide polymorphisms and 13,121 simple sequence repeats in these unigenes. Our transcriptome data provide a useful resource for future functional studies of M. aurolineatus Voss for dispersal control in tea plants.